Development of inconel 718 parts produced by metal injection molding technique for aerospace application - Suleiman @ Ahmad, Muhammad Jabir (2019)
The thesis presents the results of the investigation carried out to determine the effect of composition of the binder system and sintering cycle of metal powder binder mixture on the properties of inconel 718 sintered specimens produced by the Metal Injection Molding (MIM) technique. In this study, Inconel 718 are the nickel-based superalloys with superior materials properties range from high temperature mechanical strength, toughness to resistance to degradation in oxidizing and corrosive environment. Metal Injection Molding (MIM) is a process that has the capability to produce a component with complex shaped in high production capacity. Commonly the process requires the combination of two different types of materials; metal power and several thermoplastic materials which act as a binder system. Based on previous studies on Palm Stearin (PS), it has already classified as an alternative material for the existing binder material. PS is derived from palm oil and it has been formulated for suitability for use in the MIM process. The main advantageous of using PS in MIM process is it has various elements with differences in the weight composition and temperature. It can benefit greatly during debinding process as it can be removed gradually, thus indirectly helps in maintaining the original structure and shape of the debound part. The earlier removal of PS, helps to form capillary holes for the removal of the remaining binder. To determine the properties of sintered part using these palm oil derivative binder, a PE-PS binder system are developed with the combination of PS and Polyethylene (PE), and it is compared with conventional binder material named PE-PW-SA, combination of PE, Paraffin Wax (PW) and Stearic Acid (SA). The Inconel 718 and binder system are mixed together at 160 °C for 2 hours. The mixture of both materials is considered as feedstock were then injected molded into a tensile test shape. The binder system then was removed through the debinding process and sintered in vacuum atmosphere at 1260 °C for 6 hours with 3 different sintering cycles. The comparison are made between these specimens contain of two different binder system based on the physical and mechanical properties of Inconel 718 (IN718) sintered parts and micrograph observation. This study has discussed the effect of palm oil derivative, as compared with conventional binder systems, on the physical and mechanical properties of the injection molded Inconel 718 sintered parts sample. As an alternative binder system in MIM, the results showed that combinations of palm stearin and inconel 718 can produce sintered parts that able to meet Metal Powder Industries Federation Standard (MPIF) 35 in terms of physical and mechanical properties of the sintered MIM part and supported by good results of microstructure behavior. This has proved that palm stearin can be applied with metallic material; Inconel 718 in the production of aerospace components using metal injection molding.